2021
DOI: 10.3847/1538-3881/abf3c3
|View full text |Cite
|
Sign up to set email alerts
|

ARES.* V. No Evidence For Molecular Absorption in the HST WFC3 Spectrum of GJ 1132 b

Abstract: We present a study on the spatially scanned spectroscopic observations of the transit of GJ 1132 b, a warm (∼500 K) super-Earth (1.13 R ⊕ ) that was obtained with the G141 grism (1.125-1.650 μm) of the Wide Field Camera 3 (WFC3) on board the Hubble Space Telescope. We used the publicly available Iraclis pipeline to extract the planetary transmission spectra from the five visits and produced a precise transmission spectrum. We analyzed the spectrum using the TauREx3 atmospheric retrieval code, with which we sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 107 publications
4
49
0
Order By: Relevance
“…Swain et al (2021) analysis produced a sloped spectral feature around 1.3 µm, and a larger negative A H ≈ −0.9. The analysis of Mugnai et al (2021) and Libby-Roberts et al (2021) found instead a visibly flat spectra, and with A H close to zero. Since the last two groups return similar results, we choose to calculate A H using reduced data from Mugnai et al (2021), which is also close to the A H calculated from Libby-Roberts et al (2021).…”
Section: Transmission Data Reductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Swain et al (2021) analysis produced a sloped spectral feature around 1.3 µm, and a larger negative A H ≈ −0.9. The analysis of Mugnai et al (2021) and Libby-Roberts et al (2021) found instead a visibly flat spectra, and with A H close to zero. Since the last two groups return similar results, we choose to calculate A H using reduced data from Mugnai et al (2021), which is also close to the A H calculated from Libby-Roberts et al (2021).…”
Section: Transmission Data Reductionmentioning
confidence: 91%
“…The analysis of Mugnai et al (2021) and Libby-Roberts et al (2021) found instead a visibly flat spectra, and with A H close to zero. Since the last two groups return similar results, we choose to calculate A H using reduced data from Mugnai et al (2021), which is also close to the A H calculated from Libby-Roberts et al (2021). A trend study using uniform data reduction methods would be preferred, allowing for more rigorous comparison between exoplanets intrinsic properties (e.g., Sing et al 2016;Tsiaras et al 2018;Roudier et al 2021).…”
Section: Transmission Data Reductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent observations have probed the atmospheres of several rocky exoplanets. For example, transmission spectroscopy of GJ 1132 b has suggested an atmosphere with a high-mean-molecular-weight (high-𝜇) and/or high-altitude clouds (Southworth et al 2017;Diamond-Lowe et al 2018;Mugnai et al 2021). Similarly, transmission spectra of Trappist-1 d, e and f have ruled out clear, H 2 -rich atmospheres for these planets (de Wit et al 2018;Moran et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, transmission spectra of Trappist-1 d, e and f have ruled out clear, H 2 -rich atmospheres for these planets (de Wit et al 2018;Moran et al 2018). Furthermore, searches for molecular species such as HCN have now become possible in the atmospheres of rocky exoplanets such as 55 Cnc e and GJ 1132 b (Tsiaras et al 2016;Swain et al 2021;Mugnai et al 2021) and could provide insights into their possible interior and atmospheric conditions (e.g. Madhusudhan et al 2012).…”
Section: Introductionmentioning
confidence: 99%